Adolescent word reading in English as a foreign language. (2nd January 2020) - Prior, Anat; Zeltsman‐Kulick, Rita; Katzir, Tami
Abstract : The current study examined the proficiency of Israeli adolescents in reading single words in English, which is taught as a foreign language, and what language skills predict individual variability. Parallel measures of word reading, phonology, decoding, morpho‐syntax and vocabulary in Hebrew and English were administered to 217 adolescents in 8th and 11th grade. Following 5–8 years of English as a foreign language instruction, participants achieved reading levels commensurate with those of third to fourth grade native English‐speaking children. Decoding and vocabulary knowledge were significant predictors of single word reading across both orthographies. Morpho‐syntactic knowledge predicted word reading only in Hebrew. Further, there was pronounced variability in the extent to which phonological awareness and vocabulary predicted word reading across languages. Low levels of reading performance underline the inherent challenge in achieving reading proficiency in the complex English orthography in a foreign language setting, with limited instruction time and suboptimal pedagogy. Decoding and vocabulary are identified as important universal processes in reading, whereas differences in other predictors support script‐dependent processes in reading as well.